Enhancing Student Learning Engagement and Outcomes through the Implementation of Hollywood Square–Based Active Learning in Senior High School - Andri Dirgahayuning (INSPIRETECH GLOBAL INSIGHT, 2026)
This classroom action research investigated the implementation of the Active Learning Strategy “Hollywood Square Review” to enhance student learning activities and chemistry learning outcomes in the topic of acid–base solutions among Grade XI Science 2 students at Public Senior High School 5 Pekanbaru. The study was motivated by the teacher’s observation that students in this class demonstrated low participation during lessons, resulting in reduced learning outcomes. Limited variation in instructional strategies created a monotonous classroom atmosphere, causing students to become less enthusiastic and insufficiently motivated. To address this issue, an active learning strategy incorporating the Hollywood Square Review game was applied to create a more engaging and enjoyable learning environment. The strategy integrates a game-based tic-tac-toe quiz model adapted from the popular Hollywood Square television quiz show, designed to promote active participation through question–answer activities. This study employed collaborative classroom action research conducted over two cycles, each consisting of planning, action, observation, and reflection stages. Cycle I involved three meetings, while Cycle II involved two meetings. Data were collected through observation sheets and learning outcome tests administered at the end of each cycle. Descriptive percentage analysis was used to identify trends in student activity and performance. The findings showed that the Hollywood Square Review strategy effectively improved both learning activities and outcomes. Student activity increased from 66.07% in Cycle I to 81.65% in Cycle II. Similarly, student learning outcomes improved from 64.29% in Cycle I to 80.95% in Cycle II. These results indicate that the Hollywood Square Review strategy successfully enhanced student engagement, encouraged active participation, and improved mastery of chemistry content in the acid–base topic.